Ring finger protein 128 promotes, rather than inhibits, colorectal cancer progression by regulating the Hippo signaling pathway - Ning, Shili; Chen, Yuzhuo; Wang, Guangzhi; Liu, Yongtai; Yang, Yingchi; Zhang, Zhongtao (Frontiers in Oncology, 2022)
Background: Colorectal cancer is a common malignancy of the gastrointestinal tract, and its incidence and mortality rates have increased in recent years. RNF128 is an E3 ubiquitin ligase that plays an important role as a suppressor gene or oncogene in various cancers, but its mechanism in colorectal cancer is still controversial. The aim of this study was to investigate the role and mechanism of RNF128 in colorectal cancer. Methods: The expression of RNF128 in colorectal cancer tissues was assessed by immunohistochemistry and western blotting. The proliferation ability of colorectal cancer cells was measured by colony formation assay and CCK-8 assay, the migration and invasion ability of colorectal cancer cells was measured by wound-healing assay and Transwell assay, and the expression levels of Hippo signaling pathway proteins were examined by western blotting. In vivo, xenograft tumor formation assays were used to detect the effect of RNF128 on tumor growth. Results: The expression level of RNF128 was significantly higher in colorectal cancer tissues than in adjacent normal tissues. In LoVo cells and HCT116 cells, the proliferation, migration and invasion abilities were significantly reduced with RNF128 knockdown. In addition, knockdown of RNF128 resulted in significant activation of the Hippo signaling pathway. In in vivo experiments, the volume and weight of xenograft tumors in nude mice were significantly decreased compared with those in the normal control group with RNF128 knockdown. Conclusion: RNF128 promotes malignant tumor behaviors in colorectal cancer cells by inhibiting the Hippo signaling pathway, which may provide a new target for colorectal prevention and treatment.